Separation, identification and cardiovascular activities of phospholipid classes from the head of Penaeus vannamei by lipidomics and zebrafish models. Issue 5 (18th February 2021) - Zhang, Mengqi; Li, Peihai; Wang, Fengxia; Zhang, Shanshan; Li, Haonan; Zhang, Yun; Wang, Ximin; Liu, Kechun; Li, Xiaobin
Abstract : Five phospholipid classes of Penaeus vannamei head were separated, analyzed and quantified. They had different cardiovascular activities evaluated in zebrafish models, which may provide a research basis for pharmaceutical use of marine phospholipids. Abstract : Phospholipids not only have high nutritional value, but also have a positive effect on cardiovascular disease, cancer and nervous system diseases. However, the activity of individual phospholipid classes of shrimp phospholipids is rarely studied. This paper researched phospholipids in the by-products of Penaeus vannamei processing. The phospholipid classes of the head from P. vannamei (PV) were separated by column chromatography, analyzed with UHPLC-Q-Exactive HF/MS, and quantified using ammonium ferrothiocyarate spectrophometry. In addition, their cardiovascular activities in zebrafish models were evaluated. A total of 5 phospholipid classes were obtained, including PV-PC, PV-PE, PV-PI, PV-PS and PV-SM, and identified as phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidylserine (PS) and sphingomyelin (SM), respectively. In the phospholipid profiling analysis, PV-PC (308 molecules) had the highest proportion with 85.24%, followed by PV-PE (139 types) with 9.32%, PV-SM (41 structures) with 4.75%, PV-PS (24 types) with 0.16%, and PV-PI (6 molecules) with 0.03%. In the quantitative analysis, the content of PV was 45.7%, and the purity of phospholipid classes was 75.5–88.1%. In the cardiovascular activity assays, the effects of different phospholipid classes were different. For example, PV-PC groups had strong angiogenesis activity, but PV-PE groups showed the opposite property. Our comprehensive profiling analysis and in vivo bioactivity evaluation of phospholipids from the head of P. vannamei can provide evidence for their targeted applications in the future.